Network analysis-based strategy to investigate the protective effect of cepharanthine on rat acute respiratory distress syndrome - Chen, Chen; Wang, Ning; Wang, Bingjie; Zhang, Qiaoyun; Hu, Yuexia; Cheng, Gao; Tao, Shaoyi; Huang, Jian; Wang, Chunhui; Zhang, Ye (Frontiers in Pharmacology, 2022)
Combined with Network Analysis (NA) and in vivo experimental methods, we explored and verified the mechanism of Cepharanthine (CEP) involved in the treatment of acute respiratory distress syndrome (ARDS). Potential targets of CEP were searched using the SwissTargetPrediction database. The pathogenic genes related to ARDS were obtained using the DisGeNET database. A protein-protein interaction network of common target genes of disease-compound was subsequently built and visualised. Functional enrichment analysis was performed through the Enrichr database. Finally, for in vivo experimental verification, we established an oleic acid-induced ARDS rat model, mainly through histological evaluation and the ELISA method to evaluate both the protective effect of CEP on ARDS and its effect on inflammation. A total of 100 genes were found to be CEP targeted genes, while 153 genes were found to be associated with ARDS. The PPI network was used to illustrate the link and purpose of the genes associated with CEP and ARDS, which contained 238 nodes and 2333 links. GO and KEGG analyses indicated that inflammatory response and its related signalling pathways were closely associated with CEP-mediated ARDS treatment. Thus, a key CEP–gene–pathway-ARDS network was constructed through network analysis, including 152 nodes (5 targets and 6 pathways) and 744 links. The results of in vivo experiments showed that CEP could alleviate histopathological changes and pulmonary edema related to ARDS, in addition to reducing neutrophil infiltration and secretion of inflammatory cytokines, whilst increasing serum contents of ResolvinD1 and ResolvinE1. Thus, these effects enhance the anti-inflammatory responses. Thus, our results show that CEP can treat oleic acid-induced ARDS in rats via ResolvinE1 and ResolvinD1 signalling pathways that promote inflammation resolution, providing a new avenue to explore for the clinical treatment of ARDS.